Responsibilities of the Occupational and Environmental Medicine Provider in the Treatment and Prevention of Climate Change-Related Health Problems. Issue 2 (February 2018) - Perkison, William B.; Kearney, Gregory D.; Saberi, Pouné; Guidotti, Tee; McCarthy, Ronda; Cook-Shimanek, Margaret; Pensa, Mellisa A.; Nabeel, Ismail
Abstract : N/A: Workers are uniquely susceptible to the health hazards imposed by environmental changes. Occupational and environmental medicine (OEM) providers are at the forefront of emerging health issues pertaining to working populations including climate change, and must be prepared to recognize, respond to, and mitigate climate change-related health effects in workers. This guidance document from the American College of Occupational and Environmental Medicine focuses on North American workers health effects that may occur as a result of climate change and describes the responsibilities of the OEM provider in responding to these health challenges.